A Holocene fire history from Terra Nova National Park, Newfoundland, Canada: vegetation and climate change both influenced the fire regime - Lake, Nickolas F.; Arsenault, André; Cwynar, Les C. (Frontiers in Ecology and Evolution, 2024)
Fire is the largest natural disturbance factor in the boreal forest and plays a critical role in the composition, structure, and succession of stands and landscapes. The island of Newfoundland, located in eastern Canada, is subjected to a greater maritime influence, which may result in longer fire return intervals. The limited data on the fire regime does not account for interactions between fire, vegetation, and climate throughout the Holocene. We used sediment cores from Arnold’s Pond, Terra Nova National Park, which covered the last ~11,800 cal. yr BP, to investigate these interactions. We recognize 4 pollen zones and macroscopic charcoal analysis detected 45 local fire events. The 250-year mean fire return interval associated with the current vegetation is longer than a previous estimate for the park, but significantly shorter than other estimates for the island. Our mean fire return interval is within the range of fire estimates from Québec with similar vegetation. Our results suggest that the fire regime was primarily influenced by vegetation and climate. The transition to an open forest from a shrub tundra resulted in increased fire activity and fire frequency, which were likely driven by additional fuel on the landscape, but could have also been influenced by unknown climatic factors. We identified several examples of changes in the fire frequencies and/or charcoal accumulation that coincided with regional climate shifts, but we also identified a non-synchronous change. The non-synchronous shift to drier conditions resulted in a ~500-year time lag between peak Pinus strobus abundance and maximum fire frequency. Synchronous shifts in fire activity and/or fire frequency coincided with the 8200 event, Medieval Climate Anomaly and Little Ice Age. We also noted a decrease in fire frequency between 2600–1500 cal. yr BP that coincided with similar changes in the fire frequency from ~3000–1000 cal. yr BP in Québec. Our study highlights the complex interactions influencing the fire regime in our study area during the Holocene.